2014
DOI: 10.1519/jsc.0000000000000496
|View full text |Cite
|
Sign up to set email alerts
|

Blood Ammonia and Lactate as Markers of Muscle Metabolites During Leg Press Exercise

Abstract: To examine whether blood lactate and ammonia concentrations can be used to estimate the functional state of the muscle contractile machinery with regard to muscle lactate and adenosine triphosphate (ATP) levels during leg press exercise. Thirteen men (age, 34 ± 5 years; 1 repetition maximum leg press strength 199 ± 33 kg) performed either 5 sets of 10 repetitions to failure (5×10RF), or 10 sets of 5 repetitions not to failure (10×5RNF) with the same initial load (10RM) and interset rests (2 minutes) on 2 separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
55
2
10

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 30 publications
8
55
2
10
Order By: Relevance
“…The 5×10RF resulted in significant high levels of muscle lactate (25.0 ± 8.1 mmol/kg wet weight), blood lactate (10.3 ± 2.6 mmol/L), and blood ammonia (91.6 ± 40.5 μmol/L). During 10×5RNF no or minimal changes were observed (Gorostiaga et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The 5×10RF resulted in significant high levels of muscle lactate (25.0 ± 8.1 mmol/kg wet weight), blood lactate (10.3 ± 2.6 mmol/L), and blood ammonia (91.6 ± 40.5 μmol/L). During 10×5RNF no or minimal changes were observed (Gorostiaga et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…The mean blood lactate concentration 7 min after the induction of acidosis during the lactate minimum test was 10.79±1.65 mm/l (Altimari et al, 2010). Gorostiaga et al (Gorostiaga et al, 2014) used leg press exercise to examine blood lactate and ammonia and muscle lactate. Thirteen men participated and 1 repetition maximum leg press strength 199 ± 33 kg performed either 5 sets of 10 repetitions to failure (5×10RF), or 10 sets of 5 repetitions not to failure (10×5RNF) with the same initial load (10RM) and interset rests (2 minutes) on 2 separate sessions in random order.…”
Section: Introductionmentioning
confidence: 99%
“…Two groups of highly trained athletes practicing opposite sport disciplines were compared. Previous research has included physically active individuals but not competitive athletes [11,18,21]. Apart from the high level of sport performance, our sprinters and triathletes (all of whom are members of the Polish national team) were a very homogenous group with regards to their body build and composition, training status, training phase in the one-year cycle and, presumably, their genetic predispositions.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Gorostiaga et al [11] observed a significant correlation between the blood ammonia level and the muscle ATP, and concluded that blood ammonia could be used as an extracellular marker for muscle ATP content. Moreover, ammonia affects both the central nervous system and the muscle functioning [16,27]; thus, it is also considered as a biomarker for peripheral muscle fatigue [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation